A phenomenological investigation into undergraduate students' experience of acquiring the discourse of engineering - Van Heerden, Karen Ilse (Rhodes University, Faculty of Education, Department of Education, 2001)
The area of discourse acquisition and writing in higher education has become a much researched field. In South Africa the interest in discourse acquisition and writing has been partly in response to the change in student profile, particularly over the past ten years. While South African researchers and academics are increasingly focusing their interest in discourse acquisition and writing on the unique circumstances here, they rely on theories based on research done in very different social contexts. These theories are not necessarily universally appropriate. South Africa is currently undergoing a period of transformation in higher education aimed at greater access and equity for black students and academics. The accompanying sense of frustration and disillusionment among students and academics underlines the need to reappraise all aspects of higher education. Much of the research on discourse acquisition and writing is undertaken in arts programmes: vocational fields - such as engineering education - tend to be neglected. If the envisaged growth in science and engineering education is to be realised, it is essential that research in discourse and writing be undertaken in engineering programmes. This study investigates discourse acquisition as experienced by students in a South African engineering faculty. The experiences of six final year technikon students are investigated to gain a better understanding of what it means to acquire the discourse of engineering. The phenomenological method used requires that the researcher suspends or brackets a priori theoretical notions or pre-conceptions so that that which the students experience, rather than what the researcher expects in terms of theory, can emerge. What emerges from the students' experiences is partially congruent with established discourse and writing theories. However, some of the student experiences of discourse acquisition differ in significant ways from what is described in mainstream writing and discourse acquisition theory. The differences in the manner in which these students experience their acquisition of engineering discourse leads to a new understanding of the phenomenon. The students do not experience the alienation or struggle described in mainstream theoretic accounts of discourse acquisition. Students' approaches to writing are affected by their awareness of their multiple identities and the different locations in which they learn. Their approaches to writing are significantly different in some respects from descriptions in mainstream theories in some respects. The description of their experiences gives a different understanding of what it means to acquire the discourse of engineering, and may contribute to the reappraisal of engineering education in a contemporary South African context.
Keywords: Education, Higher -- South Africa Students -- Attitudes; Academic writing -- Study and teaching -- South Africa; English language -- Rhetoric -- Study and teaching -- South Africa; Technical writing -- Study and teaching